1980
DOI: 10.1677/joe.0.0870065
|View full text |Cite
|
Sign up to set email alerts
|

l-THYROXINE, CORTISOL AND DIET AFFECT THE LEVEL OF AMYLASE IN THE PAROTID GLAND OF DEVELOPING RATS

Abstract: The effects of cortisol (10 microgram/g body weight) and L-thyroxine (T4; 0.2 microgram/g body weight) on the activity of parotid gland amylase in young rats were investigated. Administration of cortisol or T4 for 5 consecutive days from day 5 after birth caused the precocious appearance of amylase, T4 having almost twice the effect of cortisol. Cortisol and T4 did not have synergistic effects. In thyroidectomized-adrenalectomized rats, T4 increased amylase activity but cortisol did not. The increase in enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Fetal serum corticosterone concentration is at the adult level during the last stage of gestation, rapidly declines after birth, and increases back to the adult level between 15 and 25 days of age (Takeuchi et al,1977a,1978). Maturation of the parotid acini, as assessd by α‐amylase per unit of tissue, is delayed when the postnatal rise in either thyroid or corticosteroid hormones are surgically or chemically prevented (Takeuchi et al,1977b) and precocious when either hormone is injected at 6 to 8 days of age (Sasaki et al,1976; Takeuchi et al1978; Takuma et al,1978; Kumegawa et al,1980). It should be noted that there are parallel effects on general development, e.g., eye opening and tooth eruption (Bakke et al,1975; Froelich and Meserve,1982; Gamborino et al,2001) that may influence parotid acinar maturation by means of early change from liquid to solid diet (Redman,1987).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal serum corticosterone concentration is at the adult level during the last stage of gestation, rapidly declines after birth, and increases back to the adult level between 15 and 25 days of age (Takeuchi et al,1977a,1978). Maturation of the parotid acini, as assessd by α‐amylase per unit of tissue, is delayed when the postnatal rise in either thyroid or corticosteroid hormones are surgically or chemically prevented (Takeuchi et al,1977b) and precocious when either hormone is injected at 6 to 8 days of age (Sasaki et al,1976; Takeuchi et al1978; Takuma et al,1978; Kumegawa et al,1980). It should be noted that there are parallel effects on general development, e.g., eye opening and tooth eruption (Bakke et al,1975; Froelich and Meserve,1982; Gamborino et al,2001) that may influence parotid acinar maturation by means of early change from liquid to solid diet (Redman,1987).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exogenous thyroid hormone has been shown to induce precocious rises in serum corticosterone and corticosteroid-binding globulin in rat pups (D’Agostino and Henning 1982). Exogenous corticosteroids have been shown to increase the rate of other aspects of rat and mouse salivary gland differentiation (Johannessen 1965, Sasaki et al 1976, Takeuchi et al 1977a,b, Kumegawa et al 1980, Johnson 1987, Ikeda et al 2008, Inukai et al 2008). Thus, it is possible that a T 4 -induced rise in serum corticosteroids also may have been involved in the acceleration of MEC translocation and decline in parenchymal cell proliferative activity observed here.…”
Section: Discussionmentioning
confidence: 99%
“…This permits the study of factors that influence gland development via interventions applied directly to the pups, thus avoiding modifications of the effects of application via the dams. Alterations of diet and hormones have been shown to influence strongly postnatal development of rodent salivary glands (Sasaki et al 1976, Takeuchi et al 1977a,b 1978, Takuma et al 1978, Kumegawa et al 1980, Johnson 1987, Ikeda et al 2008, Inukai et al 2008). Serum thyroid hormone concentration is low in the perinatal rat, increases to twice the adult level by 16 days of age, and returns to the adult level by 30 days (Clos et al 1974, Porterfield and Hendrick 1981, Dussault et al 1982, Porterfield 1985, Farwell and Dubord-Tomasetti 1999).…”
mentioning
confidence: 99%
“…1). It was previously reported that administration of thyroxine at an early age results in an enhanced synthesis of amylase by the parotid gland (31). Thus, it could be hypothesized that an enhanced parotid amylase content could be responsible for an enhanced baseline amylase secretion in hyperthyroid animals.…”
Section: Discussionmentioning
confidence: 99%